Asleep : The forgotten epidemic that remains one of medicine's greatest mysteries - Crosby, Molly Caldwell (New York : Berkley Books, 2010)
Crosby, acclaimed author of "The American Plague," explores the frightening history of a long forgotten disease--sleeping sickness--and details the frantic effort to conquer it before it strikes again.
An epidemic begins ; Constantin von Economo ; The London outbreak ; New York City ; Ruth ; The neurologist ; The medical investigators ; Adam ; Smith Ely Jelliffe ; The alienist ; Only the beginning ; Jessie ; 1925 ; A two-headed beast ; Madness ; Rosie ; The Neurological Institute ; The Matheson Commission ; Josephine B. Neal ; Vaccine trials ; Sylvia ; I have seen the future ; Philip ; Gray matter ; Past or prologue?
Includes bibliographical references and index.
Keywords: Epidemic encephalitis -- History; Encephalitis, Arbovirus -- epidemiology -- Europe -- Case Reports; Encephalitis, Arbovirus -- epidemiology -- United States -- Case Reports; Encephalitis, Arbovirus -- history -- Europe -- Case Reports; Encephalitis, Arbovirus -- history -- United States -- Case Reports; Disease Outbreaks -- history -- Europe -- Case Reports; Disease Outbreaks -- history -- United States -- Case Reports; History, 20th Century -- Europe -- Case Reports; History, 20th Century -- United States -- Case Reports